SCALE_UP - AN ACTIVE LEARNING CASES MODELLING AT KAUNAS UAS - Dalė Lukšaitė; Jūratė Lukšaitė; Gintarė Jurkševičiūtė (Izdevnieciba "Baltija Publishing", 2017)
The article reviews SCALE-UP (The Student-Centered Activities for Large Enrollment Undergraduate Programs) active learning environment and Cloud Computing technologies Enabled Active Learning know-how, the main requirements for a SCALE-UP type classroom and educational model. Transfer of this good practice of equipping two SCALE-UP classes at Kaunas University of Applied Sciences is discussed. This article presents the modelling case for Software Engineering, Data Management Technology, Business Economics and Management Courses. Each of those courses consists of lectures and practical activities. Three phases are underlined for each topic: 1) the problem based learning; 2) practical activities by tutoring; 3) collaborative learning. The lectures and practical work are combined and executed as a whole in the frame of SCALE-UP study plan and an active learning scenario. The classroom is equipped with a virtual workplace, cloud computing services, open resources on the Internet, e-libraries and subscribed databases. The study results considering the assessment of collaborative learning outcomes and the use of cloud computing technologies are discussed.